Case Report: Streptococcus gordonii triggering suppurative parotitis and sepsis in a patient with Sjögren syndrome - Wang, Ye; Gong, Lin-Feng; Wang, Ze-Kun; Qian, Hong-Bo; Wu, Xiao-Qing (Frontiers in Medicine, 2025)
BackgroundAcute suppurative parotitis is common in primary Sjögren syndrome due to parotid gland dysfunction. Streptococcus gordonii is an aggressive pathogen but is rarely reported in acute suppurative parotitis.Case summaryA 64-year-old woman with primary Sjögren syndrome, history of periodontitis, and recurrent parotid swelling developed acute suppurative parotitis from Streptococcus gordonii, quickly leading to sepsis. The pathogen was confirmed via pus and blood cultures, and effective antimicrobial treatment was initiated promptly, controlling the condition.ConclusionThis case highlights the rapid progression of Streptococcus gordonii-induced acute suppurative parotitis to sepsis, emphasizing the importance of primary Sjögren syndrome screening and managing periodontal infections in patients with recurrent parotid swelling.